Trends in all-cause mortality among people with diagnosed diabetes in high-income settings: a multicountry analysis of aggregate data. Issue 2 (February 2022) - Magliano, Dianna J; Chen, Lei; Carstensen, Bendix; Gregg, Edward W; Pavkov, Meda E; Salim, Agus; Andes, Linda J; Balicer, Ran; Baviera, Marta; Chan, Juliana C N; Cheng, Yiling J; Gardiner, Helene; et al.
Summary: Background: Population-level trends in mortality among people with diabetes are inadequately described. We aimed to examine the magnitude and trends in excess all-cause mortality in people with diabetes. Methods: In this retrospective, multicountry analysis, we collected aggregate data from 19 data sources in 16 high-income countries or jurisdictions (in six data sources in Asia, eight in Europe, one from Australia, and four from North America) for the period from Jan 1, 1995, to Dec 31, 2016, (or a subset of this period) on all-cause mortality in people with diagnosed total or type 2 diabetes. We collected data from administrative sources, health insurance records, registries, and a health survey. We estimated excess mortality using the standardised mortality ratio (SMR). Findings: In our dataset, there were approximately 21 million deaths during 0·5 billion person-years of follow-up among people with diagnosed diabetes. 17 of 19 data sources showed decreases in the age-standardised and sex-standardised mortality in people with diabetes, among which the annual percentage change in mortality ranged from –0·5% (95% CI –0·7 to –0·3) in Hungary to –4·2% (−4·3 to –4·1) in Hong Kong. The largest decreases in mortality were observed in east and southeast Asia, with a change of –4·2% (95% CI –4·3 to –4·1) in Hong Kong, –4·0% (−4·8 to –3·2) in South Korea, –3·5% (−4·0 to –3·0) in Taiwan, and –3·6% (−4·2 to –2·9) in Singapore. The annual estimated change in SMR between people with and without diabetes ranged from –3·0% (95% CI –3·0 to –2·9; US Medicare) to 1·6% (1·4 to 1·7; Lombardy, Italy). Among the 17 data sources with decreasing mortality among people with diabetes, we found a significant SMR increase in five data sources, no significant SMR change in four data sources, and a significant SMR decrease in eight data sources. Interpretation: All-cause mortality in diabetes has decreased in most of the high-income countries we assessed. In eight of 19 data sources analysed, mortality decreased more rapidly in people with diabetes than in those without diabetes. Further longevity gains will require continued improvement in prevention and management of diabetes. Funding: US Centers for Disease Control and Prevention, Diabetes Australia Research Program, and Victoria State Government Operational Infrastructure Support Program